2013
DOI: 10.3727/096368912x657323
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of BDNF-Overexpressing Human Neural Stem Cells (HB1.F3.BDNF) in a Rodent Model of Middle Cerebral Artery Occlusion

Abstract: Ischemic stroke mainly caused by middle cerebral artery occlusion (MCAo) represents the major type of stroke; however, there are still very limited therapeutic options for the stroke-damaged patients. In this study, we evaluated the neurogenic and therapeutic potentials of human neural stem cells (NSCs) overexpressing brain-derived neurotrophic factor (HB1.F3.BDNF) following transplantation into a rodent model of MCAo. F3.BDNF human NSCs (F3.BDNF) were transplanted into the contralateral side of striatum at 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…For those subjects who do not produce high levels of these cells, we suggest that enhancing this response could beneficial, possibly as a means of delivering BDNF to the site of injury. Other studies that support the role of BDNF in recovery after stroke showed that BDNF-expressing neural stem cells were beneficial (Chang et al, 2013), as were mesenchymal stem cells (Jeong et al, 2014). Methods such as the use of histone deacetylase inhibitors (Kim et al, 2009) or a CD28 superagonist, as have already been shown to be beneficial in experimental stroke (Na et al, 2015), are possible strategies to increase the number of Treg cells.…”
Section: Discussionmentioning
confidence: 95%
“…For those subjects who do not produce high levels of these cells, we suggest that enhancing this response could beneficial, possibly as a means of delivering BDNF to the site of injury. Other studies that support the role of BDNF in recovery after stroke showed that BDNF-expressing neural stem cells were beneficial (Chang et al, 2013), as were mesenchymal stem cells (Jeong et al, 2014). Methods such as the use of histone deacetylase inhibitors (Kim et al, 2009) or a CD28 superagonist, as have already been shown to be beneficial in experimental stroke (Na et al, 2015), are possible strategies to increase the number of Treg cells.…”
Section: Discussionmentioning
confidence: 95%
“…For functional tests, we used the rotarod test and the modified neurological severity score (mNSS) test, as described previously [26]. For the rotarod test, rats were pre-trained under the same conditions three times a day, for 3 consecutive days, before MCAo induction to reduce variation among animals.…”
Section: Functional Tests and The Measurement Of Final Infarct Sizementioning
confidence: 99%
“…GDNF has been reported to be neuroprotective 62 by promoting cell survival, but also enhances axonal outgrowth and synaptogenesis. To augment the growth factor-mediated neuroprotective potential of NSCs, therapeutic approaches that employ the induced overexpression of factors such as BDNF 63 for the treatment of ischemic stroke, or GDNF 64 for hemorrhagic stroke, have been suggested. These strategies can even be combined with the use of cytoprotectants, making transplanted NSCs more resilient against oxidative stress and reperfusion injury 65, 66 .…”
Section: Part Ii: Recovery Without Replacement and The Prevalence Of mentioning
confidence: 99%